The ecdysone regulatory pathway controls wing morphogenesis and integrin expression during Drosophila metamorphosis. - D'Avino, P.P.; Thummel, C.S. (Developmental Biology, 2000)
Drosophila imaginal discs are specified and patterned during embryonic and larval development, resulting in each cell acquiring a specific fate in the adult fly. Morphogenesis and differentiation of imaginal tissues, however, does not occur until metamorphosis, when pulses of the steroid hormone ecdysone direct these complex morphogenetic responses. In this paper, we focus on the role of ecdysone in regulating adult wing development during metamorphosis. We show that mutations in the EcR ecdysone receptor gene and crooked legs (crol), an ecdysone-inducible gene that encodes a family of zinc finger proteins, cause similar defects in wing morphogenesis and cell adhesion, indicating a role for ecdysone in these morphogenetic responses. We also show that crol and EcR mutations interact with mutations in genes encoding integrin subunits-a family of alphabeta heterodimeric cell surface receptors that mediate cell adhesion in many organisms. alpha-Integrin transcription is regulated by ecdysone in cultured larval organs and some changes in the temporal patterns of integrin expression correlate with the ecdysone titer profile during metamorphosis. Transcription of alpha- and beta-integrin subunits is also altered in crol and EcR mutants, indicating that integrin expression is dependent upon crol and EcR function. Finally, we describe a new hypomorphic mutation in EcR which indicates that different EcR isoforms can direct the development of adult appendages. This study provides evidence that ecdysone controls wing morphogenesis and cell adhesion by regulating integrin expression during metamorphosis. We also propose that ecdysone modulation of integrin expression might be widely used to control multiple aspects of adult development.